Induction Chemotherapy and Ablative Stereotactic Magnetic Resonance Image-Guided Adaptive Radiation Therapy for Inoperable Pancreas Cancer - Chuong, Michael D.; Herrera, Roberto; Kaiser, Adeel; Rubens, Muni; Romaguera, Tino; Alvarez, Diane; Kotecha, Rupesh; Hall, Matthew D.; McCulloch, James; Ucar, Antonio; DeZarraga, Fernando; Aparo, Santiago; et al. (Frontiers in Oncology, 2022)
Background Radiation therapy (RT) dose for inoperable pancreatic ductal adenocarcinoma (PDAC) has historically been non-ablative to avoid injuring gastrointestinal (GI) organs at risk (OARs). Accruing data suggest that dose escalation, in select patients, may significantly improve clinical outcomes. Early results of ablative stereotactic magnetic resonance image-guided adaptive radiation therapy (A-SMART) have been encouraging, although long-term outcomes are not well understood. Methods A single institution retrospective analysis was performed of inoperable non-metastatic PDAC patients who received induction chemotherapy then 5-fraction A-SMART on a 0.35T-MR Linac from 2018-2021. Results Sixty-two patients were evaluated with a median age of 66 years (range 35-91) and nearly all achieved Eastern Cooperative Oncology Group (ECOG) performance status 0-1 (96.8%). Locally advanced disease was common (72.6%), otherwise borderline resectable (22.6%), or medically inoperable (4.8%). All received induction chemotherapy for a median 4.2 months (range, 0.2-13.3) most commonly FOLFIRINOX (n=43; 69.4%). Median prescribed dose was 50 Gy (range 40-50); median biologically effective dose (BED10) was 100 Gy10. The median local control (LC), progression-free survival (PFS), and overall survival (OS) from diagnosis were not reached, 20 months, and 23 months, respectively. Also, 2-year LC, PFS, and OS were 68.8%, 40.0%, and 45.5%, respectively. Acute and late grade 3+ toxicity rates were 4.8% and 4.8%, respectively. Conclusions To our knowledge, this is the largest series of induction chemotherapy followed by ablative 5-fraction SMART delivered on an MR Linac for inoperable PDAC. The potential for this novel treatment strategy is to achieve long-term LC and OS, compared to chemotherapy alone, and warrants prospective evaluation.